Malignant Mesothelioma Advances in Pathogenesis, Diagnosis, and Translational Therapies - Pass, Harvey I.; Vogelzang, Nicholas J.; Carbone, Michele; SpringerLink (Online service) (New York, NY : Springer New York, 2005)
no bcc - textbook design.
Carcinogenesis -- The History of Mesothelioma -- Asbestos-Induced Mesothelioma -- SV40-Mediated Oncogenesis -- Mesothelioma Carcinogenesis: In Vivo Models -- Mesothelial and Mesothelioma Cell Lines -- Molecular Genetics -- Cytogenetics of Malignant Mesothelioma -- Growth Factors and Malignant Mesothelioma -- Oncogenes and Tumor Suppressor Genes in Malignant Mesothelioma -- Angiogenesis and Mesothelioma -- Immune Status and Mesothelioma -- Extracellular Matrix and Mesothelioma: Some Clues to the Invasive Behavior of Mesothelioma -- Genomics and Proteomics in Mesothelioma -- Epidemiology -- Asbestos Mineralogy and Health Effects -- Molecular Epidemiology of Mesothelioma -- Malignant Mesothelioma and Erionite -- Determination of Asbestos Exposure by Pathology and Clinical History -- Mesothelioma and Asbestos Exposure -- From Monkey to Man: The Epidemiologic Evidence of an Association Between Simian Virus 40 and Malignancy -- Causes and Prevention of Technical Artifacts When Studying Simian Virus 40 (SV40) in Human Mesotheliomas -- Molecular Detection of Siman Virus 40 in Human Mesothelioma -- Malignant Mesothelioma Following Radiation -- Genetics and Human Mesothelioma -- Clinical Presentation -- Clinicians$1 (BApproach to Mesothelioma -- Clinical Presentation and Natural History of Mesothelioma: Pleural and Pericardial -- Clinical Presentation and Natural History of Mesothelioma: Abdominal -- Staging of Mesothelioma -- Prognostic Factors in Mesothelioma -- Imaging and Endoscopy -- Radiologic Assessment of Mesothelioma -- Endoscopic Imaging -- Pathology -- Benign Mesotheliomas, Mesothelial Proliferations, and Their Possible Association with Asbestos Exposure -- Cytology of Malignant Mesothelioma -- Immunohistochemistry -- Malignant Mesothelioma Electron Microscopy -- Rare Variants of Mesothelioma -- Differentiating Sarcomas from Mesotheliomas -- Diagnosis of Synovial Sarcoma of the Pleura and Differentiation from Malignant Mesothelioma -- Pitfalls in the Diagnosis of Malignant Mesothelioma -- Treatment -- Management of Benign Variants of Mesothelioma -- First-Line Chemotherapy for Malignant Pleural Mesothelioma -- Second-Line Chemotherapy -- Treatment of Mesothelioma with Radiotherapy -- Multimodality Approaches -- Intrapleural Chemotherapy with and Without Surgery in Malignant Pleural Mesothelioma (MPM) -- Management of Pleural Effusions in Mesothelioma -- Preoperative Chemotherapy and Surgery -- Photodynamic Therapy for Pleural Mesothelioma -- Surgery and Postoperative Radiotherapy -- The Development of the Brigham and Women$1 (Bs Multimodality Treatment Plan for Malignant Pleural Mesothelioma: A Model for Improving the Treatment of Rare Diseases -- Peritoneal Mesothelioma: The Columbia Experience -- Surgery, Hyperthermic Chemoperfusion, and Postoperative Chemotherapy: The National Cancer Institute and Washington Hospital Center Experience -- Pericardial and Tunica Vaginalis Mesothelioma -- Novel Treatment Strategies -- New Target Therapies for Malignant Mesothelioma -- Gene Therapy for Malignant Pleural Mesothelioma -- Immunotherapeutic Approaches and Vaccination Strategies -- Economic Implications -- Economic Aspects of Mesothelioma.s
Keywords: Medicine; Oncology; Thoracic surgery; Medicine & Public Health; Oncology; Thoracic Surgery; Electronic books